Prenatal Sonographic Features of Fetuses in Trisomy 13 Pregnancies (IV) - Chih-Ping Chen (Elsevier, 2010)
Prenatal ultrasound is a powerful tool to detect structural abnormalities associated with the fetuses in trisomy 13 pregnancies. This article provides a comprehensive review of the prenatal sonographic markers of trisomy 13 in the first trimester, including fetal nuchal translucency thickness, fetal heart rate, fetal nasal bone, fetal tricuspid regurgitation, ductus venous flow, fetal crown-rump length, fetal trunk and head volume, fetal frontomaxillary facial angle, gestational sac volume and umbilical cord diameter, along with biochemical markers such as maternal serum free β-human chorionic gonadotropin, maternal serum pregnancy-associated plasma protein-A, maternal serum placental growth factor, and the fetal and total cell-free DNA concentration in the maternal circulation.